2007
DOI: 10.1038/sj.emboj.7601906
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies of neuropilin/antibody complexes provide insights into semaphorin and VEGF binding

Abstract: Neuropilins (Nrps) are co‐receptors for class 3 semaphorins and vascular endothelial growth factors and important for the development of the nervous system and the vasculature. The extracellular portion of Nrp is composed of two domains that are essential for semaphorin binding (a1a2), two domains necessary for VEGF binding (b1b2), and one domain critical for receptor dimerization (c). We report several crystal structures of Nrp1 and Nrp2 fragments alone and in complex with antibodies that selectively block ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
195
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(206 citation statements)
references
References 63 publications
9
195
1
1
Order By: Relevance
“…Hence, it was initially suggested that Sema3s compete for the binding to Nrp1 with VEGF, thus inhibiting VEGF-induced angiogenesis. However, recent reports have shown that Sema3s and VEGF use different domains on Nrp1 for binding [40]. Consistent with a separate function of Sema3A on Nrp1, Sema3A increases vascular permeability, inhibits endothelial cell proliferation, and induces apoptosis even in the absence of VEGF [34,41], suggesting Sema3A activates its own signaling routes.…”
Section: Sema3amentioning
confidence: 78%
“…Hence, it was initially suggested that Sema3s compete for the binding to Nrp1 with VEGF, thus inhibiting VEGF-induced angiogenesis. However, recent reports have shown that Sema3s and VEGF use different domains on Nrp1 for binding [40]. Consistent with a separate function of Sema3A on Nrp1, Sema3A increases vascular permeability, inhibits endothelial cell proliferation, and induces apoptosis even in the absence of VEGF [34,41], suggesting Sema3A activates its own signaling routes.…”
Section: Sema3amentioning
confidence: 78%
“…The NRP cytoplasmic domain has 40 residues and allows binding of the PDZ domain-containing protein GIPC1 (or synectin) 49 . NRP1 can form ligand-independent homodimers 29 , and heterodimers with NRP2 63-65 and with VEGFR2 48 , 49 in the cellular plasma membrane. NRP1 (but not NRP2) has one covalent GAG (HS/CS) attachment in the EC domain at Serine 612 30 (conserved across species 66 ); The GAG modification of NRP1 enhances VEGFR2 signaling in endothelial cells by multiple mechanisms, including enhancement of VEGF-A165a binding and delayed degradation of VEGFR2 bound to VEGF 30 . …”
Section: Vegf-a Isoforms Exhibit Differential Binding To Vegfrs and Nrpsmentioning
confidence: 99%
“…16). The MAM domain has been suggested to have a role in dimerization of NRPs (31); however, other reports suggest the importance of the CUB and F5/8 domains as well as the transmembrane region in NRP dimerization (32)(33)(34). Recently, Rollenhagen et al (35) showed that NRP-2 is polysialylated on O-glycans located in the linker region between the second F5/8 (F5/8-2) and MAM domains.…”
Section: Resultsmentioning
confidence: 99%